2003 Kansas Performance Tests with Summer Annual Forages - Roozeboom, Kraig L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
This publication presents the results of tests designed to compare forage production and quality of corn, sorghum, and sorghum-sudan hybrids. Samples from each harvest were collected to determine moisture content and for laboratory analysis of forage quality.
Keywords: Kansas; Summer annual forages; Crude protein; Neutral detergent fiber; Acid detergent fiber; Acid detergent lignin; Forage yield; Forage moisture